NAMDEV DHASAL: THE FIRE OF POETRY AND ACTIVISM AGAINST CASTE - Bute, Amol; Banana, Lakshmanarao; Srinivasarao, Chaduvula; Majji, Eswara Rao (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Namdev Dhasal is known as an important figure in Indian literature. Simultaneously, he was the social activist. His works represented the untouchability and goes beyond the boundaries of art and politics. He is a co-founder of the Dalit Panther Movement and the author of groundbreaking works like Golpitha. He used his poetry to challenge the rooted hierarchies of the caste system and redefine Dalit identity. He born into the Mahar community in Maharashtra. His lived experiences of marginalization and oppression deeply influenced his writing, which is characterized by its raw, steady portrayal of Dalit life and its militant call for social justice. This paper try to explore how the poetry of Dhasal dismantles caste-based oppression and reimagines dalit identity as one of resistance and empowerment. By analyzing his major works within the context of the Dalit Panther Movement, this study aims to shed light on his unique contribution to both literature and social justice, as well as his enduring legacy in the fight for caste equality.